2013
DOI: 10.1097/cmr.0b013e32835efd8d
|View full text |Cite
|
Sign up to set email alerts
|

Effect of paclitaxel/carboplatin salvage chemotherapy in noncutaneous versus cutaneous metastatic melanoma

Abstract: Little is known about the efficacy of salvage chemotherapy for patients with metastatic, noncutaneous melanoma after the failure of dacarbazine-based chemotherapy. Because of the high incidence of noncutaneous melanoma in Korea, we assessed the outcomes of paclitaxel/carboplatin (PC) salvage chemotherapy in patients with noncutaneous metastatic melanoma. We retrospectively analyzed patients with metastatic melanoma who received intravenous paclitaxel (175 mg/m) plus intravenous carboplatin (area under the curv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 28 publications
0
15
1
2
Order By: Relevance
“…However, many series questioned the value of extensive, radical operations for mucosal tumors, which are associated with extremely high risk of systemic recurrence . Recent small studies have suggested a survival benefit for adjuvant chemotherapy in MM, although larger studies are needed to validate these findings . Our data indicate that patients with MM may not achieve optimal survival despite high rates of aggressive local resections and radiotherapy, and their associated morbidity.…”
Section: Discussionmentioning
confidence: 73%
“…However, many series questioned the value of extensive, radical operations for mucosal tumors, which are associated with extremely high risk of systemic recurrence . Recent small studies have suggested a survival benefit for adjuvant chemotherapy in MM, although larger studies are needed to validate these findings . Our data indicate that patients with MM may not achieve optimal survival despite high rates of aggressive local resections and radiotherapy, and their associated morbidity.…”
Section: Discussionmentioning
confidence: 73%
“…This classification, missing T1 and T2 stages, can be attributed to the aggressive local growth pattern of this tumor entity with irregular borders, melanosis, and in-transit metastases [9]. conventional chemotherapies have not so far shown any significant benefit [10][11][12].…”
Section: Introductionmentioning
confidence: 98%
“…The median PFS was 2.53 months in all patients, and 21.9% of them achieved PR. No significant difference was observed between MM patients and cutaneous melanoma patients, indicating that paclitaxel combined with carboplatin may also be a reasonable option for metastatic MM patients who have received multi-line treatment (189).…”
Section: Adjuvant Chemotherapymentioning
confidence: 94%